European Airway Management Society (EAMS) structure and activities - SARAÇOĞLU, AYTEN (ELSEVIER SCI LTD, 2018)
European Airway Management Society (EAMS) was created as a multi-disciplinary society to provide a forum for health professionals interested in airway management. The foundation meeting was held during the European Society of Anesthesiology (ESA) Congress in June 2003. Since 2009, the EAMS Hands-on Airway Workshop has been organized during the annual congresses of the European Society of Anaesthesiologists (Euroanaesthesia congress) as a one-day precongress course. EAMS is eager to create a learning environment with small groups custom-made training in advanced airway management using simulated airway scenarios. By this way participants gain practice skills and strategies for the management of airway emergencies. EAMS created 6 committees: Committee on EAMS Development and Communication, Annual Meeting & Sponsoring Committee, Education & Trainee Committee, Advisory Committee, Science Committee and Airway Management in Special Circumstances Committee, and in all committees are Board of Directors (BOD) members represented. In conclusion EAMS is a growing non-profit society aiming to disseminate and promote the exchange of information in regard to airway management. EAMS is open for new members, new ideas and concepts, new scientific approaches to airway management and educational strategies to teach and learn airway management. (c) 2017 Published by Elsevier Ltd.
Keywords: Airway management; EAMS; Society